2011
DOI: 10.1186/1471-2334-11-128
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices (KAP) related to the Pandemic (H1N1) 2009 among Chinese General Population: a Telephone Survey

Abstract: BackgroundChina is at greatest risk of the Pandemic (H1N1) 2009 due to its huge population and high residential density. The unclear comprehension and negative attitudes towards the emerging infectious disease among general population may lead to unnecessary worry and even panic. The objective of this study was to investigate the Chinese public response to H1N1 pandemic and provide baseline data to develop public education campaigns in response to future outbreaks.MethodsA close-ended questionnaire developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
132
6
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(175 citation statements)
references
References 22 publications
19
132
6
11
Order By: Relevance
“…Our findings indicated that knowledge was the most common predictor for these four protective behaviors. Knowledge of protective behaviors against influenza was associated with perceived changes in protective behaviors and an intent to receive an influenza vaccine, which is similar to the study among lay people and nurses [34,35], but inconsistent with previous findings regarding the intent to receive the H1N1 vaccine [4,36]. Although educational level was not associated with perceived changes in protective behaviors, similar to the H1N1 outbreak in Sweden [20], this finding contrasts with those of other studies [32,34,37].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Our findings indicated that knowledge was the most common predictor for these four protective behaviors. Knowledge of protective behaviors against influenza was associated with perceived changes in protective behaviors and an intent to receive an influenza vaccine, which is similar to the study among lay people and nurses [34,35], but inconsistent with previous findings regarding the intent to receive the H1N1 vaccine [4,36]. Although educational level was not associated with perceived changes in protective behaviors, similar to the H1N1 outbreak in Sweden [20], this finding contrasts with those of other studies [32,34,37].…”
Section: Discussioncontrasting
confidence: 72%
“…Additionally, age was collapsed into three groups (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and 50 and above), and educational level was measured with four levels (primary and under, junior high school, senior high school, and college and above).…”
Section: Predictorsmentioning
confidence: 99%
“…This study result has a clear significance association between illiteracy of village midwives and general knowledge and attitude regarding Hepatitis B virus. Usually knowledge, attitude and practices regarding health subjects are associated with literacy [19,20]. A study in Sudan among health care workers reflected that educated health care workers have adequate level of knowledge about Hepatitis B virus, while the illiterate labors have very low level of knowledge [21].…”
Section: Resultsmentioning
confidence: 99%
“…61,71-73 Slightly higher levels were reported outside Europe, 74,75 and coverage in the US reached about 25%. 76 As a consequence of all these factors many countries were left with large stockpiles of unused vaccine, and health authorities were blamed for mismanaging the preparedness efforts and for wasting public funds.…”
Section: Vaccination Of Males Against Human Papilloma Virus: Acceptanmentioning
confidence: 99%